2013
DOI: 10.1139/cjfas-2013-0164
|View full text |Cite
|
Sign up to set email alerts
|

Fishway passage bottleneck identification and prioritization: a case study of Pacific lamprey at Bonneville Dam

Abstract: 26Fishways designed for salmonids often restrict passage by non-salmonids and effective tools are 27 needed both to identify passage problems for non-target species and to inform remediation 28 planning. In this case study, we used migration histories from 2170 radio-tagged adult Pacific 29 lamprey (Entosphenus tridentatus) to identify locations of poor passage ("bottlenecks") at a 30 large, multi-fishway dam. Over ten years, 49% of tagged lamprey that entered fishways failed to 31 pass the dam. Models account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…The lack of a body size effect in network metrics suggests while size selection occurs at the dam‐wide scale, size‐selectivity is weak at local scales (this study; Keefer et al . ). It may also be that these size‐selective processes are associated with genotype (Hess et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lack of a body size effect in network metrics suggests while size selection occurs at the dam‐wide scale, size‐selectivity is weak at local scales (this study; Keefer et al . ). It may also be that these size‐selective processes are associated with genotype (Hess et al .…”
Section: Discussionmentioning
confidence: 97%
“…burst‐swimming speed), structural impediments and environmental factors may explain the low passage rates observed for Pacific lamprey at Columbia River dams compared to salmon (Keefer et al . , ; Johnson et al . ; Kirk et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the type and function of specific dams, migration pathways of fish (e.g. potamodromous and anadromous species) are impacted at different levels (Haxton & Findley, ; Keefer et al., ; Nilsson, Reidy, Dynesius, & Revenga, ). Quantifying emigration rates with a goal to maintain/establish a MVP are essential components in a recovery plan when evaluating stocking strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In western North America, studies have shown that fewer than 50 % of adult Pacific lamprey encountering the lower Columbia River hydroelectric dams were able to negotiate the fishways (Moser et al 2002a, b;Keefer et al 2013), and dams in some tributaries (e.g., the Umatilla and Snake rivers) and the upper Columbia River are largely impassable to lampreys (see Ward et al 2012). In the Yakima River subbasin in south-central Oregon, for example, an average of only 20 adult lamprey are now observed returning per year (Patrick Luke, Yakama Nation, Toppenish, WA, personal communication, 2013).…”
Section: Barriers To Passagementioning
confidence: 99%